Smart Branding Award: Assessing Digital Brand Awareness and Image of the Recipients - Asshagab, Sri Milawati (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2024)
City branding refers to a government initiative to highlight a local region’s distinctiveness and competitive strengths to increase citizen satisfaction and pride, attract tourists and investments, and stimulate the local economy. In contemporary times, the practice of city branding can be enhanced through the utilization of information and communication technology to introduce the potential of a region, referred to as smart branding. This research aims to expand our understanding of smart branding in Indonesia by examining the Smart City Award given by the Ministry of Communication and Information, which only granted the Smart Branding Award to 15 out of 145 regions in 2021. The methodology employed in this study is a qualitative research design, utilizing a descriptive statistical approach and content analysis. The study found that some regions awarded the Smart Branding Award lack favorable brand awareness and image due to low rankings of government websites, insufficient website and social media management, and negative sentiments in online news and comments, highlighting the need for local governments to prioritize citizen engagement and information dissemination to strengthen their position and attract investment and tourism for sustainable economic and social benefits. Continuous improvement of digital branding is also crucial to adapt to digital trends.